Effect of ethephon and irrigation deficit on color enhancement of Vitis vinifera L. as determined by anthocyanin content of wine - Poxleitner, Marianne, author; Stushnoff, Cecil, advisor (Colorado State University. Libraries, 1999)
Three experiments were performed on Colorado grown grapevines to test irrigation deficit and/or ethephon application on the color enhancement of red wines. In the first experiment, drip irrigated Pinot noir vines were exposed to an irrigation deficit in the second half of the growing season. Vine water potential was monitored with a pressure bomb, and resulting wines were analyzed spectrophotometrically for anthocyanin content. No significant increase in anthocyanins was found between the wines from the control and treatment groups. The second experiment used Sangiovese grapevines to test the application of a 750 ppm ethephon spray at eight weeks and nine weeks post anthesis against a control. Spectrophotometric analysis of the wines showed significant increases in anthocyanin content of 16.7% and 41.7% above the control for the eight and nine week post anthesis applications, respectively. The third experiment utilized furrow irrigated Pinot noir vines to test the effects of ethephon on vines subjected to a late season water deficit. A pressure bomb was used to monitor vine water potential, a neutron probe was used to monitor soil moisture, and the wines were analyzed spectrophotometrically. A significant increase in anthocyanin content was found due to the ethephon application at nine weeks post anthesis to the vines subjected to the water stress. A final experiment was conducted to observe the differences in color between Pinot noir and Merlot wines from different Colorado wineries. In addition, the color variation between different cultivars of wines from the Orchard Mesa Research Center was also investigated. Significant differences were found between the Pinot noir wines as well as the Merlot wines, and between the various cultivars analyzed.
Covers not scanned.
Keywords: Viticulture; Plant-water relationships; Plants -- Effect of ethephon on; Anthocyanins